TB Treatment Delays in Odisha, India: Is It Expected Even after These Many Years of RNTCP Implementation? - Kumaravel Ilangovan; Sharath Burugina Nagaraja; Ramya Ananthakrishnan; Anil G Jacob; Jaya Prasad Tripathy; Deepak Tamang (PLoS ONE, 2015)
In India, the Revised National TB Control Programme (RNTCP) envisages initiation of TB treatment within seven days of diagnosis among smear-positive patients. After nearly two decades of RNTCP implementation, treatment delays are usually not expected.To determine the proportion of sputum smear-positive TB patients who were initiated on treatment after seven days and their associated risk factors.The study was conducted in Cuttack and Rayagada districts of Odisha. It was a retrospective cohort study that involves review of TB treatment registers and laboratory registers for 2013.Among 1,800 pulmonary TB (PTB) patients, 1,074 (60%) had been initiated on treatment within seven days of diagnosis, 721 (40%) had been initiated on treatment more than seven days, and 354 (20%) had delays of more than 15 days. The mean duration between TB diagnosis and treatment initiation was 21 days with a range of 8-207 days (median = 14 days). Odds of treatment delay of more than seven days were 4.9 times (95% confidence interval [CI] 3.3-6.6) among those who had been previously treated, 6.2 times (95% CI 1.3-29.7) among those infected with HIV, and 1.8 times (95% CI 1.1-2.9) among those diagnosed outside district DMC.Delay in initiation of TB treatment occurred in majority of the smear-positive patients. The RNTCP should focus on core areas of providing quality TB services with time-tested strategies. To have real-time monitoring mechanisms for diagnosed smear-positive TB patients is expected to be the way forward.